Off‐great‐circle paths in transequatorial propagation: 1. Discrete and diffuse types. Issue 11 (5th November 2016) - Tsunoda, Roland T.; Maruyama, Takashi; Tsugawa, Takuya; Yokoyama, Tatsuhiro; Ishii, Mamoru; Nguyen, Trang T.; Ogawa, Tadahiko; Nishioka, Michi
Abstract: There is mounting evidence that plasma structure in nighttime equatorial F layer evolves from large‐scale wave structure (LSWS) in the bottomside F layer. This process cannot be ignored because equatorial plasma bubbles (EPBs) arise from large‐amplitude LSWS; and, because intense radiowave scintillations are associated with EPBs, understanding the LSWS‐to‐EPB process is a crucial step toward reliable Space Weather Forecasting. In this regard, the transequatorial propagation (TEP) experiment appears to be the most useful among available research instruments. After a lapse of 30 years, the TEP experiment has been resurrected; a goal of this research is to understand TEP measurements well enough so that they can be used to diagnose the LSWS‐to‐EPB process. Toward this end, new results are presented in two companion papers. Herein (P1), off‐great‐circle (OGC) propagation paths are shown to consist of two types, discrete and diffuse. The new findings include the following: (1) a generalized multireflection model that can explain most of the observed properties; (2) the discrete type is supported by multireflections from an unstructured upwelling, (3) the diffuse type is supported by reflections from plasma structure in EPBs; and (4) the observed east‐west (EW) asymmetry can be explained in terms of a distorted upwelling or plasma structure along the west wall of an upwelling. In Paper 2 (P2), a second form of observed EW asymmetry is explained in terms of plasma structure, which is not aligned with the geomagnetic field. The findings strongly confirm a close relationship between upwellings, ESF patches, and OGC paths. Key Points: Two types of TEP paths in nighttime equatorial F layer, discrete, and diffuse Off‐great‐circle paths are related to upwellings and equatorial plasma bubbles Multireflection model is introduced to explain properties of off‐great‐circle paths